2013
DOI: 10.4236/ojpc.2013.34019
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Eumelanin in Generating Reactive Oxygen and Reactive Nitrogen in Solution: Possible Relevance to Keloid Formation

Abstract: Recently, nitric oxide (NO) has been implicated as an epigenetic factor in keloids, a scarring disease occurring primarily in dark skinned people who have relatively high amounts of pigment melanin. In this work, we tested whether a melanin-mediated redox reaction involving adsorbed NO and O 2 can couple NO oxidation with O 2 reduction to form reactive oxygen species (ROS) or reactive nitrogen species (RNS) in vitro at pH 7.4. We measured the formation of reactive species that oxidize dihydrorhodamine123 (DHR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…To see whether there is a connection between the presence of pigment per se and the occurrence of keloids, we tested a system containing an aerated solution of sepia melanin and NO for evidence of a chemisorption mechanism. We demonstrated that sepia melanin scavenges NO . The data provided a good fit ( r 2 = 0.94) to a Langmuir adsorption isotherm, with pseudo first‐order rate constant k ′ = 8.2 × 10 7 s −1 and adsorption coefficient K ad = 4.04 L mol −1 (Fig.…”
Section: Adsorption Of Compounds To Melaninmentioning
confidence: 62%
See 2 more Smart Citations
“…To see whether there is a connection between the presence of pigment per se and the occurrence of keloids, we tested a system containing an aerated solution of sepia melanin and NO for evidence of a chemisorption mechanism. We demonstrated that sepia melanin scavenges NO . The data provided a good fit ( r 2 = 0.94) to a Langmuir adsorption isotherm, with pseudo first‐order rate constant k ′ = 8.2 × 10 7 s −1 and adsorption coefficient K ad = 4.04 L mol −1 (Fig.…”
Section: Adsorption Of Compounds To Melaninmentioning
confidence: 62%
“…Given its ability to conduct electrons and protons, we have been interested in whether melanin can couple redox reactions between adsorbed electron donor and acceptor molecules of biological or commercial relevance. Depending on the system, in vivo coupling of this sort can lead to beneficial or adverse consequences.…”
Section: Adsorption Of Compounds To Melaninmentioning
confidence: 99%
See 1 more Smart Citation